Język reklamy jako narzędzie perswazji i manipulacji na przykładzie wybranych polskich spotów telewizyjnych - Fus, Agnieszka (Investigationes Linguisticae, 2010)
This article concerns language devices, which are used in television commercials and which are a manner of persuasion and manipulation. The important part of this article is to present the most popular slogans, their influence on us – consumers and the correlation between language of the television commercials and colloquial language. Not only will I focus on neologisms, which introduce the atmosphere of unusualness and convince a receiver about special advantages of the advertised products, but also on the phenomenon of anthropomorphism and personification. This article shows, how authors of television commercials manipulate their consumers, i.a. by introducing created by themselves terms, which imitate scientific terms and apply implicature and presupposition. All described language phenomena are presented on chosen by me examples from Polish television commercials.